Дослідження впливу характеристик окремих елементів металоконструкції на стійкості палетних стелажів - Гнатенко, Григорій Олександрович; Коваленко, Валентин Олександрович; Рубашка, Володимир Петрович; Стрижак, Всеволод Вікторович; Турчин, Ольга Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2025)
В статті розглядаються питання аналізу чутливості стійкості стелажної конструкції до зміни жорстких параметрів її основних конструктивних елементів – стійок, балок та розкосів. Аналіз чутливості проводиться на основі розробленої 3-D моделі стелажу, що враховує топологію стелажу, властивості всіх складових елементів та особливості зав’язків, що поєднують ці елементи в єдину пружну конструкцію. На основі розрахунку коефіцієнтів чутливості визначено внесок жорстких параметрів кожного елемента у стійкість усієї системи.

The article considers the issues of analyzing the sensitivity of the stability of a rack structure to changes in the rigid parameters of its main structural elements - racks, beams and braces. These elastic elements have their own stiffness properties and are in a constant force relationship when the rack is loaded, so the parameters of each of them contribute to the stability of the elastic structure. Clarification of the elements whose parameters make the greatest contribution to the stability of the elastic structure will open up the possibility of influencing stability by changing the elastic parameters of these elements. The sensitivity analysis of the stability of the rack to changes in the parameters of the component elements is the subject of this article. The sensitivity analysis is carried out on the basis of the developed 3-D model of the rack, which takes into account the topology of the rack, the properties of all component elements and the features of the ties that combine these elements into a single elastic structure. To implement this approach, the increment method was used, based on the alternate change of one input parameter while fixing the others and calculating the increase in the output parameter of the model. It helps to understand how individual input variables affect the final result, and to assess the degree to which output indicators depend on changes in data, assumptions, or conditions. Based on the calculation of sensitivity coefficients, the contribution of the rigid parameters of each element to the stability of the entire system is determined
Research on the influence of the characteristics of individual elements of metal structure on the stability of pallet racks
Keywords: стелажі; балки; розкіс; стійкість; коефіцієнт запасу стійкості; аналіз чутливості; коефіцієнти чутливості; rack; beam; brace; stability; safety factor; sensitivity analysis; sensitivity factors